Copper-vapor low intensity laser therapy; CIS Selected Papers: Laser Use in Oncolog, December 31, 1995, Russia - Zyryanov B. N.; Evtushenko V. A.; Evtushenko G. S. Gennady Sergeevich; Soldatov A. N.; Musabaeva L. I.; Udalyi I. F.; Tarasenko T. I.; Cherdyntseva N. V.; Vusik M. V.; Popovich V. I.; Petrakova V. S.; Dikovich V. A. (1995, 1995)
Title screen